AN ANALYSIS OF TOURISM AND HOSPITALITY POTENTIAL ON EMPLOYMENT GENERATION IN METROPOLITANT KANO STATE, NIGERIA - Aliyu, S. M.; Ibrahim, B. L. (FUDMA JOURNAL OF SCIENCES, 2023)
The paper analyzed the tourism and hospitality potential on employment generation in metropolitan Kano state, Nigeria. The objectives are to; identify the number of registered hospitality industries, factors responsible for the growth of hospitality industry and their contribution. The study adopts survey research method. The sampled were drawn from officials of Kano state tourism Management Board and Hoteliers Association of Nigeria, Kano State Chapter in a purposive manner. Key Informant Interview; semi-structured questionnaire were used as tools of data generation: and simple statistical tool was adopted for analysis. The findings revealed that only 85 hotels registered with Kano state tourism Management board with Fagge LGA had 63.5 % being the highest numberof hotels while Kumbotso LGA had 1.2% which is the least number of Hotels. The industry provides employment to over 6,430 people and generates about 32,295,122.37 million to KSMB between 2013 to 2016. Provision of Accommodation, Constructions and Renovations and other facilities, establishment of Hospitality and tourism institute and free land for investors are some of the strategy adopt by the government to promote tourism in the state. The major challenges of tourism development in the state includes; Power Supply, Insufficient Fund, Lack of Autonomy and Excessive Tariff. The study Recommend that, adequate power supply, funds, autonomy to Kano state tourism Management Board should be taken into considerations.